Analysis of Termination of Prosecution in Drug Abuse Cases Based on Restorative Justice - Made Suarja Teja Buana, Anak Agung; Winjaya Laksana, Andri (UNISSULA Semarang, 2025)
Imprisonment of narcotics and dangerous drug users has proven ineffective. This is a common thread in law enforcement against narcotics users. The purpose of this study is to examine and analyze the implementation of the termination of prosecution for narcotics abuse cases based on restorative justice, examine and analyze weaknesses in the termination of prosecution for narcotics abuse cases based on restorative justice. This legal research uses an empirical juridical legal research approach. The implementation of the termination of prosecution for narcotics abuse cases in Indonesia is still based on Law No. 35 of 2009, specifically Article 127 paragraph (1), which positions users as criminal perpetrators, thus causing overcrowding in prisons and social stigma. To address this, the Attorney General's Office issued Attorney General's Guidelines No. 18 of 2021 which opened the opportunity for termination of prosecution with a rehabilitation mechanism, although previously Regulation No. 15 of 2020 excluded narcotics cases. Real implementation is evident in the Eros Prastiyo case at the Sidoarjo District Attorney's Office, which demonstrates the restorative justice process, from pre-prosecution and BNN assessment to rehabilitation. This approach emphasizes punishment as the ultimum remedium and positions users as victims in need of recovery. However, its implementation still faces substantive weaknesses, such as articles that emphasize imprisonment over rehabilitation. Furthermore, structural weaknesses are evident in inter-institutional coordination, limited rehabilitation facilities, and weak oversight. Weaknesses in the legal culture, such as societal stigma and a repressive paradigm by officials, remain dominant. Therefore, reforms in the substance, structure, and culture of the law are needed to create a more humane and just system.